2012
DOI: 10.1021/tx300066z
|View full text |Cite
|
Sign up to set email alerts
|

Generation of DNA-Damaging Reactive Oxygen Species via the Autoxidation of Hydrogen Sulfide under Physiologically Relevant Conditions: Chemistry Relevant to Both the Genotoxic and Cell Signaling Properties of H2S

Abstract: Hydrogen sulfide (H2S) has long been known for its toxic properties; however, in recent years, evidence has emerged that this small, gaseous molecule may serve as an endogenous cell-signaling agent. Though perhaps surprising in light of its potential role as an endogenous signaling agent, a number of studies have provided evidence that H2S is a DNA-damaging mutagen. In the work reported here, the chemical mechanisms of DNA damage by H2S were examined. Using a plasmid-based DNA strand cleavage assay, it was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 98 publications
1
38
0
Order By: Relevance
“…Production of oxygen in the presence of sulfide is tied to severe toxification risks by reactive oxygen species (ROS) generation (Latifi et al, 2009; Hoffman et al, 2012). A counterbalancing advantage of such adaptation strategy remains mysterious to us – especially in the modern world where potential competitors for space and resources [e.g., SOB and obligate anoxygenic phototrophs (Klatt et al, 2016)] as well as microorganisms that might affect this competition via feedback mechanisms on the S- and C-cycle (e.g., sulfate reducers) have developed sophisticated strategies to cope with fluctuating oxygen and sulfide concentrations (e.g., Blankenship and Matsuura, 2003; Baumgartner et al, 2006; Berghoff et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Production of oxygen in the presence of sulfide is tied to severe toxification risks by reactive oxygen species (ROS) generation (Latifi et al, 2009; Hoffman et al, 2012). A counterbalancing advantage of such adaptation strategy remains mysterious to us – especially in the modern world where potential competitors for space and resources [e.g., SOB and obligate anoxygenic phototrophs (Klatt et al, 2016)] as well as microorganisms that might affect this competition via feedback mechanisms on the S- and C-cycle (e.g., sulfate reducers) have developed sophisticated strategies to cope with fluctuating oxygen and sulfide concentrations (e.g., Blankenship and Matsuura, 2003; Baumgartner et al, 2006; Berghoff et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al concluded that the reaction is too slow overall to be biologically relevant [35]. However, metals [123,126,127,134–139] (also see 5.2.2 ) and other biological substances such as phenols and aldehydes [134] can accelerate the reaction. Indeed, it has been known since 1958 that certain metalloprotein complexes (including ferritin) can catalyze H 2 S oxidation [140].…”
Section: H2s Reaction With Oxidantsmentioning
confidence: 99%
“…This suggests that in cells H 2 S could function biologically to mask the chelatable or labile iron pool and prevent formation of highly reactive oxygen species and thus contribute to its salutatory function in a variety of pathologies involving disturbances in O 2 , a possibility for which there is indeed evidence [224]. However, as mentioned in 4.1 , metal catalyzes H 2 S autoxidation that causes reactive oxygen species formation and consequent oxidative damage to cellular components (including DNA) [139]. …”
Section: H2s Reaction With Metalsmentioning
confidence: 99%
“…However, as most of the metal catalysts used in the previous study were redox active, they would nicely fit into our mechanisms involving sulfhydryl radical species formation as a starting point. 32 …”
Section: Reaction Between 8-no 2 -Gua and H 2 S In The Presence Of Tmentioning
confidence: 99%